Unleashing the Power of DevOps : Revolutionizing Software Development Practices - Ashish Dewakar Pandey,; Kavita Narendrabhai Parmar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of development and operations, popularly known as DevOps, has emerged as a transformative force in modern software development practices. This review paper delves into the multifaceted landscape of DevOps, exploring its principles, methodologies, and the profound impact it has on software development processes. Through an examination of historical evolution, cultural shifts, and technological advancements, the paper elucidates how DevOps fosters collaboration, automation, and continuous improvement across the software development lifecycle. Furthermore, it investigates the challenges and opportunities associated with implementing DevOps practices, including cultural barriers, security considerations, and the adoption of cloud technologies. By synthesizing insights from industry best practices, case studies, and academic research, this paper provides a comprehensive overview of the principles and practices that underpin the successful adoption of DevOps. Ultimately, it underscores the potential of DevOps to revolutionize software development, empowering organizations to deliver high-quality software products with speed, efficiency, and agility.
Keywords: Software Development Lifecycle; DevOps; Revolutionizing Software